A new approach to modelling micro-explosions in composite droplets - Sazhin, S.S. (Elsevier Ltd, 2020)
A new approach to modelling puffing and micro-explosion in composite water/fuel droplets is proposed. This approach is based on the assumption previously made that a spherical water sub-droplet is located in the centre of a spherical fuel (n-dodecane) droplet. The heating of a fuel droplet is described by the heat conduction equation with the Robin boundary condition at its surface and continuity conditions at the fuel-water interface. The analytical solution to this equation, obtained at each time step, is incorporated into the numerical code and used for the analysis of droplet heating and evaporation. The effects of droplet thermal swelling are taken into account. The results of calculations using this code allowed us to obtain the time evolution of the temperature at the water/fuel interface and the evolution of time derivative of this temperature (TË) with time in the same location. Using the original and previously published experimental data, two new correlations for the nucleation temperatures TN as functions of TË, valid in the range 0â¤TËâ¤106 K/s, are suggested. Using these correlations and the values of TË inferred from the analysis, the time evolutions of the nucleation temperatures TN at the water-fuel interface are obtained. The predicted values of TN are compared with the values of temperature at this interface Tw. The time instant when Tw=TN is associated with the time instant when puffing/micro-explosion starts. Â© 2020 Elsevier Ltd